Blue Ocean Strategy Analysis PT Mandom Indonesia TBK - Hidayat, Angela Nathania (Syntax Literate, 2025)
The cosmetics industry in Indonesia is experiencing rapid growth, driven by urbanization, digitalization, and shifting consumer trends, with an estimated annual growth rate of 5.35%. Amid intense competition, PT Mandom Indonesia Tbk, a leading cosmetics company, seeks to differentiate itself through a Blue Ocean Strategy. This study aims to analyze PT Mandom’s internal and external environments and propose innovative strategies to create an uncontested market space. Using secondary data from annual reports, financial statements, and industry analyses, the research employs frameworks such as PESTLE, Porter’s Five Forces, and the Six Paths Framework to assess opportunities and challenges. Key findings reveal that PT Mandom’s strengths lie in its strong financial condition, export performance, and sustainability practices, while external threats include low consumer loyalty and rising competition from local brands. The study recommends adopting augmented reality (AR) technology for virtual try-ons, forging partnerships with healthcare and baby-care industries, and establishing salon/spa facilities to enhance emotional and functional product appeals. Additionally, the company should prioritize product innovation, brand image, and market share while deprioritizing non-critical factors like environmental regulations. These strategies aim to position PT Mandom in a blue ocean, leveraging Indonesia’s demographic and technological trends. The research implications highlight the need for empirical validation of these initiatives, particularly their impact on consumer engagement and market expansion, while balancing innovation with sustainability concerns in a dynamic industry.